Pharmacogenetics and phenoconversion: the influence on side effects experienced by psychiatric patients - den Uil, Manon G.; Hut, Hannelotte W.; Wagelaar, Kay R.; Abdullah-Koolmees, Heshu; Cahn, Wiepke; Wilting, Ingeborg; Deneer, Vera H. M. (Frontiers in Genetics, 2023)
Introduction: Preventing side effects is important to ensure optimal psychopharmacotherapy and therapeutic adherence among psychiatric patients. Obtaining the pharmacogenetic profile of CYP2C19 and CYP2D6 can play an important role in this. When the genotype-predicted phenotype shifts because of the use of co-medication, this is called phenoconversion. The aim was to study the influence of the pharmacogenetic (PGx) profile and phenoconversion on side effects experienced by psychiatric patients. Methods: A retrospective cohort study was performed using data from 117 patients from a psychiatric outpatient clinic. Patients were genotyped with a psychiatric PGx panel and side effects were evaluated using the Udvalg for Kliniske Undersølgelser side effects rating scale (UKU). Results: Of all patients, 10.3% and 9.4% underwent phenoconversion for CYP2C19 and CYP2D6 respectively. No significant associations were found between the phenotype and UKU-score. 75% of the patients with an IM or PM phenoconverted phenotype of CYP2C19 experienced nausea and vomiting compared to 9.1% of the NM and IM patients (p=0.033). 64% of the patients with an IM or PM phenoconverted phenotype of CYP2D6 experienced the side effect depression compared to 30.4% NMs and UMs (p=0.020). CYP2D6 IM and PM patients had a higher concentration-dose ratio than NM patients (p<0.05). Discussion: This study underlines the importance to consider phenoconversion when looking at a patient’s genotype. This is important for a better prediction of the phenotype and preventing possible side effects under a specific psychopharmacotherapy.